2010
DOI: 10.1351/pac-con-09-10-02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular clips and tweezers on enzymatic reactions by binding coenzymes and basic amino acids

Abstract: The tetramethylene-bridged molecular tweezers bearing lithium methanephosphonate or dilithium phosphate substituents in the central benzene or naphthalene spacer-unit and the dimethylene-bridged clips containing naphthalene or anthracene sidewalls substituted by lithium methanephosphonate, dilithium phosphate, or sodium sulfate groups in the central benzene spacer-unit are water-soluble. The molecular clips having planar naphthalene sidewalls bind flat aromatic guest molecules preferentially, for example, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…We found that CLR01, but not CLR03, neutralized the positive surface charge of SEVI, PAP85-120, and SEM1(49-107) fibrils within minutes ( Figure 4A ). Notably, pre-treatment of CLR01 with lysine or poly-L-lysine abrogated the fibril neutralizing activity of CLR01 ( Figure 4—figure supplement 1 ), which further supports previous findings concerning the specificity underlying these interactions ( Fokkens et al, 2005 ; Klärner et al, 2006 , 2010 ). Next, confocal microscopy was used to assess whether this neutralization could abrogate fibril binding to YFP-tagged virions.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We found that CLR01, but not CLR03, neutralized the positive surface charge of SEVI, PAP85-120, and SEM1(49-107) fibrils within minutes ( Figure 4A ). Notably, pre-treatment of CLR01 with lysine or poly-L-lysine abrogated the fibril neutralizing activity of CLR01 ( Figure 4—figure supplement 1 ), which further supports previous findings concerning the specificity underlying these interactions ( Fokkens et al, 2005 ; Klärner et al, 2006 , 2010 ). Next, confocal microscopy was used to assess whether this neutralization could abrogate fibril binding to YFP-tagged virions.…”
Section: Resultssupporting
confidence: 90%
“…The lysine- and arginine-specific molecular tweezer, CLR01 ( Figure 1A,B ) ( Fokkens et al, 2005 ; Klärner et al, 2006 , 2010 ), inhibits amyloid fibrillization by engaging specific lysine, arginine, or both residues within a variety of disease-associated amyloidogenic proteins including amyloid-β protein (Aβ), tau, islet amyloid polypeptide, transthyretin, and α-synuclein ( Sinha et al, 2011 ; Attar et al, 2012 ; Prabhudesai et al, 2012 ; Sinha et al, 2012 ; Acharya et al, 2014 ; Ferreira et al, 2014 ; Lopes et al, 2015 ; Zheng et al, 2015 ). Furthermore, CLR01 has even been found to slowly remodel preformed Aβ and α-synuclein fibrils over the course of several weeks ( Sinha et al, 2011 ; Prabhudesai et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crown ethers and cryptands, calixarenes and cucurbiturils all benefit from this design, albeit with the disadvantage that it favors cyclic or symmetric guests. [4][5][6][7][8][9][10][11][12][13] These draw the biologically active part of the respective cofactor (NAD + or NADP + ) [5,6,9] or amino acid (the side chain of Lys and Arg) [5][6][7][8][9][10][11][12][13][14] into their cavities, which enables them to reversibly inhibit enzymatic processes as well as protein aggregation events. [1][2][3] Among other things, the introduction of new side arms that can be accommodated within the interior of the macrocycle must be strictly avoided, because this severely impedes guest inclusion.…”
Section: Introductionmentioning
confidence: 99%
“…The new entities will posses a well-defined structure in solution and be capable of binding other molecules. Thus a vast array of functional supramolecular architectures (capsules, tweezers, clips, e.t.c) has be created (1,2,3,4,5,6).…”
mentioning
confidence: 99%